The economics of scientific misconduct : fraud, replication failure, and research ethics in empirical inquiry - Wible, James R., 1951- (New York, NY : Routledge, 2023)
"The Economics of Scientific Misconduct explores episodes of misconduct in the natural and biomedical sciences and replication failure in economics and psychology over the past half century. Here scientific misconduct is considered from the perspective of a single discipline such as economics likely for the first time in intellectual history. Research misconduct has become an important concern across many natural, medical, and social sciences, including economics, over the past half century. Initially, a mainstream economic approach to science and scientific misconduct is taken drawn on conventional microeconomics and the theories of Becker, Ehrlich, and C. S. Peirce's "economy of research." Then the works of Peirce and Thorstein Veblen from the 19th century point toward contemporary debates over statistical inference in econometrics and the failure of recent macroeconomic models. In more contemporary economics, clashes regarding discrimination and harassment have led to a Code of Professional Conduct from the American Economic Association and a Code of Ethics from one of its members. The last chapter considers research ethics matters related to the Covid 19 Pandemic. There has been an explosion of research and some retractions. More generally, a concern with research ethics contributes to scientific progress by making some of its most difficult problems more transparent and understandable and thus possibly more surmountable. This book offers valuable insights for students and scholars of research ethics across the sciences, philosophy of science and social science, and economic theory"--
Keywords: Research -- Economic aspects; Research -- Moral and ethical aspects; Science -- Social aspects; Fraud in science; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Theory